2010
DOI: 10.1111/j.1365-2788.2010.01284.x
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between motor performance and executive functioning in children with intellectual disabilities

Abstract: The current results support the notion that besides being impaired in qualitative motor skills intellectually challenged children are also impaired in higher-order executive functions. The deficits in the two domains are interrelated, so early interventions boosting their motor and cognitive development are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
173
0
19

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(205 citation statements)
references
References 55 publications
(107 reference statements)
13
173
0
19
Order By: Relevance
“…al., 2000) beyond neuroscience. For example, it has been shown that EFs are good predictors of intelligence in children (Brydges, Reid, Fox, & Anderson, 2012) and that intellectually impaired individuals have poor EFs (Hartman, Houwen, Scherder, Visscher, 2010).…”
Section: Working Memorymentioning
confidence: 99%
“…al., 2000) beyond neuroscience. For example, it has been shown that EFs are good predictors of intelligence in children (Brydges, Reid, Fox, & Anderson, 2012) and that intellectually impaired individuals have poor EFs (Hartman, Houwen, Scherder, Visscher, 2010).…”
Section: Working Memorymentioning
confidence: 99%
“…Истраживања везана за моторичке способности деце са сметњама у развоју показују да она заостају за својим вршњацима типичног развоја (Bala i sar., 1984, Golubović i sar., 2012Hartman et al, 2010;Maksimović i sar., 2012;Nikolić i Ilić, 2007). Карактеристике моторичких способности деце с интелектуалним сметњама су: ограничења и успореност у развоју моторике (Frey & Chow, 2006;Hartman et al, 2010;Vuijk et al, 2010;Westendorp et al, 2011); квалитативни недостаци у извођењу покрета и дефицит у организацији и планирању покрета у односу на циљ; присуство сувишних и несврсисходних покрета, недовољна визуомоторна координација (Gligorović Jovanović, 2000;Nikolić i sar., 2005).…”
Section: моторичке способности ученика са сметњама у развојуunclassified
“…Карактеристике моторичких способности деце с интелектуалним сметњама су: ограничења и успореност у развоју моторике (Frey & Chow, 2006;Hartman et al, 2010;Vuijk et al, 2010;Westendorp et al, 2011); квалитативни недостаци у извођењу покрета и дефицит у организацији и планирању покрета у односу на циљ; присуство сувишних и несврсисходних покрета, недовољна визуомоторна координација (Gligorović Jovanović, 2000;Nikolić i sar., 2005). Нижа постигнућа у моторичким способностима код особа с интелектуалним сметњама огледају се и у брзини и координацији покрета (Bala i sar., 1984;Nikolić i Ilić, 2007).…”
Section: моторичке способности ученика са сметњама у развојуunclassified
“…The task was originally developed as a means of assessing planning, which Shallice (1982) argued was subject to selective impairment following lesions to the left frontal lobe. While some subsequent neuropsychological studies have failed to replicate the left frontal deficit reported by Shallice (e.g., Cockburn, 1995, but see Glosser & Goodglass, 1990, and Morris et al, 1997, the task remains popular as a tool for assessing executive functioning, particularly in clinical and neuropsychological populations (e.g., Donders & Larsen, 2012;Köstering et al, 2012;Marzocchi et al, 2008;Rainville, et al 2012; see Sullivan et al, 2009, for a meta-analysis) as well as in normally and atypically developing children and adolescents (e.g., Albert & Steinberg, 2011;Bull et al, 2004;Hartman et al, 2010;Kaller et al, 2008;Luciana et al, 2009). …”
Section: Introductionmentioning
confidence: 99%